A Place at the Table: The Political Integration of Muslims in Kenya, 1963–2007 - Bakari, Mohamed (Islamic Africa, 2013)
Kenyan Muslims are well integrated within the Kenyan political system. This process of political integration gained momentum when President Daniel Arap Moi regained power after the aborted military coup attempt by the Kenya Air Force in August 1982. His increasingly authoritarian rule faced a challenge from the younger generation of politicians who began to challenge his legitimacy because of the loss of basic democratic rights through mass demonstrations and civil disobedience. A new generation of Muslim politicians and activists joined the fray. This new Muslim leadership was the product of social transformations that were ushered in by new educational opportunities that presented themselves immediately after Kenya gained independence. Muslims were able to be integrated gradually within the political system through social mobility and pragmatic policies of Jomo Kenyatta and later through the politics of cronyism and co-option under Moi. With the widening of political space and the new politics of inclusion, Muslims have now been completely integrated within Kenyan society.